The Journey Home: Lived Experiences of Emerging Adults Converting to Catholicism in a Philippine Highly Urbanized City - Recaido, Evalyn; Madrigal, Dennis V. (Technium Social Sciences Journal, 2026)
This qualitative descriptive phenomenology explores the lived experiences of five emerging adults in Bacolod City who converted to Catholicism from other Christian denominations. Utilizing Lichtman’s "Three Cs" framework, the study identifies a transformative "Journey Home" structured around three overarching themes: pre-conversion struggles, motivations during transition, and post-conversion joys. Participants initially grappled with spiritual emptiness, personal doubts, and fears of social rejection. Their transition was driven by intellectual conviction, an attraction to Catholic devotions like the Rosary, and the supportive guidance of spiritual mentors. Ultimately, conversion culminated in profound joy, characterized by a deepened relationship with God and a commitment to active Church service. These findings offer a framework for developing tailored catechesis and evangelization programs that address the unique emotional and intellectual needs of young converts.